The Analysis of Figurative Language Used in The Islamic Song Lyrics of Palestine by Irfan Makki - Xfaldo Amora Kelbi; Leni Marlina (Universitas Negeri Padang, 2023)
Figurative language uses words in unconventional ways, deviating from their usual meaning and order. This study focuses on symbolic language in Islamic song lyrics, specifically those by Irfan Makki from Palestine. It aims to analyze the different types of figurative language and their significance in the lyrics. Employing a descriptive qualitative method, the research centers on metaphorical phrases in Makki's Islamic song lyrics. By using H. M. Abrams' (1999) theory on figurative language types, the research identifies 3 instances of hyperbole, metaphor, and personification, 2 instances of metonymy and symbol, and 1 instance each of allusion, irony, and simile among the 15 data samples. The most prominent types found are hyperbole, metaphor, and personification.